Cyberstalking Legal Frameworks in the Digital Age: A Comparative Analysis of the United Kingdom, United States of America and Pakistan - Wajahat, Johar; Tarana, Marghzar; Gul, Seema (The Lighthouse Journal of Social Sciences, 2024)
Cyberstalking has become one of the most communal subjects in the digital world, creating a pressing need for sound legal frameworks to address its complexities and mitigate harm to victims. This research conducts a comparative analysis of cyberstalking laws in the United States, the United Kingdom, and Pakistan to evaluate the efficacy, scope, and enforcement of existing legislation. In the United States, federal and state laws, such as the Interstate Communications Act of 2012 and the Protection from Harassment Act, address various aspects of cyberstalking, including harassment, threats, and extortion. Similarly, the United Kingdom’s Protection of Freedoms Act 2012 and Online Safety Act 2023 provide a more advanced framework, with provisions for both minor and severe offenses, focusing on accountability. On the other hand, Pakistan’s Prevention of Electronic Crimes Act (PECA) 2016 barely covers cyberstalking issues and primarily deals with the misuse of electronic communication. This study highlights the critical gaps in Pakistan’s legal structure and analyzes how legislation developed in the United States and the United Kingdom could inform reforms. By emphasizing international best practices, this research aims to contribute toward creating more comprehensive cyberstalking laws in Pakistan that enhance victim protection and align with global standards.